TEACHING ENGLISH VOCABULARY WITH AUGMENTED REALITY(AR) FOR EFL LEARNERS. - Fazliddinova Zulfiyakhon Dilmurod qizi (Research Focus International Scientific Journal, 2025)
Technological tools in the field of education is advancing, so that there are many opportunities, especially AR,VR, online platforms. This study aims to review the lates 10 researches done in the field of AR, and its usage in teaching vocabulary to EFL learners and the effect on students language acquisition. A systematic review has been done of the last 5years researches and several word families are shown to EFL young learners to find out AR’s effect. The results indicate that all researches were positively influenced to the students’ language learning, in addition students, motivation and engagement had increased a lot.